Gaining reconciliation when living with insulin treated diabetes: a qualitative study using content analysis. Issue 1 (31st December 2022) - Eriksson, Susanne; Gustafsson, Lena-Karin
ABSTRACT: Purpose: The aim was to describe experiences of the reconciliation process when living with insulin treated diabetes. Methods: The study has a qualitative descriptive design, based upon nineteen in- depth interviews with persons diagnosed with insulin treated diabetes, analysed using qualitative content analysis. Results: The study show the reconciliation process during different time periods that appeared as domains in the interviews. The time at diagnosis showed experiences of striving for control getting insights and knowledge. It meant striving for control of life circumstance changes, supported by professionals but also from others. In Presence showed developing strategies as a tool struggling for balance in body and life and the need of evaluating relations to others. Future was sometimes avoided as this might lead to speculations about a future life with threats and uncertainty about disease complications, as well as adaption. This meant on the same time an uncertainty, as a degree of risk-taking and hope for the best. Conclusions: Persons with insulin treated diabetes need to develop flexible strategies for daily life to continuously re-evaluate their planning for attaining reconciliation. A conclusion is also that these persons need to develop a flexible regime that facilitates both quality of life and medical outcomes to reach reconciliation.